Sales promotion and consumer buying behavior for FMCGs in Kathmandu - Rai, Bharat; Bhandari, Dila Ram (NCC Journal, 2021)
The objective of the research was to identify the factors influencing buying behavior of consumers on fast-moving consumer goods in Kathmandu. The independent variables to measure consumer buying behavior are taken free samples, price discounts, and “buy one get one free” on FMCGs buying. The study used positivist epistemology with predetermined hypotheses and a deductive approach with a single ontological foundation. The study used a quantitative method. To obtain the primary data, a questionnaire which was based on a 7-point Likert scale was utilized. The population for this study was comprised of customers of fast-moving consumer goods and a sample size of 395 was used. In this study, a convenient sampling technique and a causal- comparative research design were used. Multiple regression analysis was used to identify the effect of free samples, price discounts, and “buy one get one free” on consumer behavior. The result of regression analysis found that price discounts and free samples had a significant effect on buying behavior of consumers. In contrast, the buy one gets one free has not significantly affected consumer buying behavior on FMCGs. The results provide future scholars and business people with a road map to view the emerging context of market development.